Singularities of University Pedagogical Counseling: the case of the Federal University of São Carlos - Helmer, Ester Almeida (2023)
This article presents part of the results of a research on university pedagogical advisory in Higher Education institutions in Argentina, Brazil, Portugal and Uruguay. The main objective of the project was to systematize advisory concepts and practices in different countries, identifying their singularities and synchronicities. This text focuses on data obtained through questionnaires applied to pedagogical advisors and professors at the Federal University of São Carlos (UFSCar), in Brazil. Five pedagogical advisors and six professors participated in the research. The results reveal that, although advisors recognize the positive impact of their activities on improving teaching and learning, they feel dissatisfied with the recognition and legitimacy of their work in the academic community and the adherence of professors to activities. Participating professors, in general, recognize the importance of training activities and pedagogical advisory to improve their teaching practices. They value the opportunity to acquire new knowledge, exchange experiences and reflect on their work as educators. In conclusion, the study highlights the importance of university pedagogical advisory and emphasizes the need for greater recognition and institutional support for this service. The results obtained can contribute to the dissemination of pedagogical advisory, in addition to supporting future research in this area.